Pengaruh Model Pembelajaran Artikulasi terhadap Hasil Belajar Ekonomi Siswa Kelas X Semester Genap SMA Muhammadiyah 2 Bandar Lampung - Fitria, Nur (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2016)
The problems that occurred in SMA Muhammadiyah 2 Bandar Lampung allegedly because of the lack of involvement and active participation of students in the learning process, the lack of student interest and learning model selection is less varied in increasing student activity in learning activities. The purpose of this study was to determine whether there is influence learning model articulation on learning outcomes of economy of the even semester students of class X SMA Muhammadiyah 2 Bandar Lampung in academic year 2015/2016. The method used in this research is the experimental method. The population in this research was 158 people, divided into 4 classes. To determine the sample in this study, the authors used cluster random sampling technique, the experimental class was XD and XA as the control class. The calculation result of hypothesis testing that has been done with the author, obtained t-hit = 5.33 and of the distribution tables at the level of 5% was obtained t-tab = 2.00 and thus proved that t-hit> t-tab. It can be concluded that